Penyalahgunaan Posisi Dominan Market Leader Dalam Konteks Hukum Persaingan Usaha Di Indonesia - Ammar Ichsan; Nurhasanah Nurhasanah; Indra Rahmatullah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This research is motivated by the government's efforts to enforce business competition law by issuing Law Number 5 of 1999 concerning in Prohibition of Monopolistic Practices and Unfair Business Competition. he existence of Law Number 5 of 1999 on the existing facts still raises several legal problems one of them is the extraterritorial framework. This research uses a normative -juridical approach where this research puts law as a norm building system. The norm system used in this research is based on the law regulation by Law Number 5 of 1999 and the Business Competition Supervisory Commission (KPPU) case. The conclusion of this research indicates the description of the implementation of business competition law by the Business Competition Supervisory Commission (KPPU) based on the law regulation by Law Number 5 of 1999.